THE EFFECT OF INTEGRITY AND COMMUNICATION ON EMPLOYEE PERFORMANCE IN FANAYAMA DISTRICT OFFICE, NIAS SELATAN DISTRICT - Fajar Oktavianus Manao, Fajar (Universitas Nias Raya, 2023)
The iproblem iin ithis iresearch iis ithat ithe iemployees iof ithe iFanayama isub-district ioffice icarry iout iwork iwith ia ilack iof icommitment iand iresponsibility ifor ithe iwork igiven, iinteractions ithat iare iless ieffective iin icommunicating. iThe ipurpose iof ithis istudy iwas ito idetermine ithe ieffect iof iintegrity iand icommunication ion ithe iperformance iof iemployees iof ithe iFanayama isub-district ioffice, iSouth iNias iRegency. iThis itype iof iresearch iis iquantitative iresearch iwith ian iassociative iapproach. iThe iresults iof ithe istudy iare i(1) iIntegrity i(XI) ihas ia ipositive iand isignificant ieffect ion iemployee iperformance i(Y) iat ithe iFanayama iSub-district ioffice, iSouth iNias iRegency, i(2) iCommunication i(X2) ihas ia ipositive iand isignificant ieffect ion iemployee iperformance i(Y) iand i(3) iIntegrity i(X1) iand icommunication i(X2) ihave ia ipositive iand isignificant ieffect ion iemployee iperformance i(Y). iSuggestions iare i1) i1) iThe iintegrity iof ieach iemployee ineeds ito ibe iimproved iby ifostering ihonesty iin icompleting iwork ientrusted iby ithe ileadership, i2) iThere iis iself-disclosure, iespecially iin icommunicating iwith ifellow iemployees, iand i3) iThe iability iof iemployees ito icomplete iwork ineeds ito ibe iimproved iso ithat iit ican iaffect iperformance.